2018
DOI: 10.1371/journal.pone.0208512
|View full text |Cite
|
Sign up to set email alerts
|

Climatic factors shaping intraspecific leaf trait variation of a neotropical tree along a rainfall gradient

Abstract: Intraspecific trait variation has been singled out as an important mechanism by which individuals can cope with environmental variations and avoid local extinctions. Here we evaluate variation in metamer traits (i.e., traits associated with internodes, petioles and their corresponding leaves) and parameters of chlorophyll fluorescence within and among populations of a neotropical tree, Copaifera langsdorffii. We also evaluated phenotypic plasticity in natural settings comparing traits between shade and sun-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 89 publications
2
41
0
4
Order By: Relevance
“…Although previous experimental and observational studies have shown relevant effect of water availability on intraspecific trait variability (Aspinwall et al, 2017; Souza et al, 2018), changes in precipitation and humidity along elevation are still often neglected in elevational gradient studies as it is often difficult to collect and integrate rainfall data (and snow precipitation) in studies conducted in complex mountain areas (Graae et al, 2012; Körner, 2007). While survival and germination responses were not affected positively by precipitation change (the latter, even showed a slightly negative relationship with MAP change), growth and reproductive outputs increased with positive MAP change under the ‘foreign vs. local’ comparison, with transplanted plants improving their performance compared to local individuals only when introduced in sites with higher precipitation compared to their site of origin, irrespective of the direction of transplant along elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous experimental and observational studies have shown relevant effect of water availability on intraspecific trait variability (Aspinwall et al, 2017; Souza et al, 2018), changes in precipitation and humidity along elevation are still often neglected in elevational gradient studies as it is often difficult to collect and integrate rainfall data (and snow precipitation) in studies conducted in complex mountain areas (Graae et al, 2012; Körner, 2007). While survival and germination responses were not affected positively by precipitation change (the latter, even showed a slightly negative relationship with MAP change), growth and reproductive outputs increased with positive MAP change under the ‘foreign vs. local’ comparison, with transplanted plants improving their performance compared to local individuals only when introduced in sites with higher precipitation compared to their site of origin, irrespective of the direction of transplant along elevation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that climatic variation affects leaf traits (e.g., Ehleringer & Mooney, 1978;Gregory-Wodzicki, 2000;Galmés et al, 2007;Nicotra et al, 2010;Peppe et al, 2011). The petiole length is related to the hydraulic and biomechanical aspects of the leaves, and a shorter leaf petiole length was reported for trees growing in drier regions (Souza et al, 2018). A marked latitudinal gradient in leaf margin entirety was found a century ago (Bailey & Sinnott, 1916), together with ample evidence supporting a close relationship between wood anatomy and climate (e.g., Pittermann et al, 2012 on drought affecting the evolution of the xylem tissue).…”
Section: Potential Ecological Drivers Of Nyssa Evolutionmentioning
confidence: 99%
“…The study was done in a private reserve (16° 40'03.2" S, 43° 48'35.6" W), located in the municipality of Montes Claros, Minas Gerais, Brazil. The reserve has an area of about 20 ha and soil is characterized as nutrient-poor dystrophic red-yellow latosol (Souza et al 2018). The climate is semi-arid, with well-defined dry and rainy seasons: the dry season occurs from March to October, and the rainy season occurs from November to February.…”
Section: Study Areamentioning
confidence: 99%
“…Copaifera langsdorffii (Fabaceae) is a tropical tree species of wide geographical distribution. This species presents complete deciduousness during the dry season of the year and a diverse fauna of gall-inducing insects (Fagundes 2014;Souza et al 2018). By using this system, we evaluated the role of plant architecture and interspecific competition in the organization of gall-inducing insect communities associated with adult (tree) and young (shrub) of C. langsdorffii individuals.…”
Section: Introductionmentioning
confidence: 99%